An analysis of supplier development issues in global context: an approach of fuzzy based modelling. Issue 3 (1st January 2012) - Kumar, Pravin; Shankar, Ravi; Yadav, Surendra S.
This paper aims to model the supplier development issues in global perspectives under informational vagueness. A Fuzzy Quality Function Deployment (FQFD) model has been used to correlate the buyers' needs with Suppliers' attributes. This approach supports buyers' linguistic vague input in correlation matrix. On the basis of fuzzy correlation, importances of different suppliers' attributes are determined. It is found that the approach is suitable in converting buyers' unclear or vague requirements into products/services offered by supplier. FQFD is more complex than conventional Quality Function Deployment. However, this approach helps to investigate the global issues with their importance in supplier development programme.